Pengindeksan dan capaian dokumen dalam pangkalan data teks bebas : satu pendekatan - Kari, Sarudin; Mat Yatim, Safie; Nik Mat, Nik Zalbiha (Penerbit UTM Press, 1990)

(untitled)
Free text database is considered something unusual and different from conventional databases. Records in this database are documents which have no fixed structure or forms. Hence, databases of this kind requires a different kind of data or documents manipulation because of the unconventionality of the techniques used in indexing the database. This paper discusses all process which are involved in building a large free text database management system. In addition of that, documents indexing and retrieval techniques will also be discussed.